The Effects of Different Drying Methods on the In Vitro Bioaccessibility of Phenolics, Antioxidant Capacity, and Morphology of European Plums (Prunes domestica L.) - Yener, Elif; Saroglu, Oznur; Sagdic, Osman; Karadag, Ayse (AMER CHEMICAL SOC, 2024)
Four different drying methods, hot-air-drying (HAD), vacuum-drying (VD), ultrasound-assisted vacuum-drying (US-VD), and freeze-drying (FD), were used to obtain dried plums (Prunes domestica L.). These prunes were evaluated for their physical properties (such as color, rehydration ratio, and microstructural properties), phenolic compounds, and antioxidant activities before and after being subjected to in vitro digestion. TPC (total phenolic content) of plums ranged from 196.84 to 919.58 mg of GAE (gallic acid equivalent)/100 g of dw, and neochlorogenic acid was the most abundant phenolic compound. FD prunes had the highest levels of phenolics, whereas US-VD caused the most significant loss. During in vitro digestion, the phenolics were present at higher levels at the gastric medium but failed to maintain their stability at the small intestinal stage. Among the samples, FD along with HAD prunes exhibited a higher bioaccessibility index for most of the phenolic compounds. The ratios of TPC, TFC (total flavonoid content), and individual phenolics determined in the digested residues to the initial values of the undigested samples ranged from 0.23 to 31.03%. It could be concluded that the majority of the phenolics were extracted during digestion. Our findings showed that the different drying methods would alter the microstructure, which would affect the extractability and release of phenolics in the simulated digestion model.
Keywords: PHYSICOCHEMICAL PROPERTIES; POLYPHENOLIC CONTENT; PROFILES; FOOD; PHYTOCHEMICALS; DIGESTION; FRUITS; FRESH; QUANTIFICATION; ANTHOCYANINS; Chemistry